How Should Teachers View Learner Code Switching in Second/ Foreign Language Classrooms? - Sari Hidayati (Universitas PGRI Semarang, 2016)
This article aims to discuss functions of code switching in second and foreign language classrooms. The discussion focuses on learner (as opposed to teacher) code switching in classrooms in which the learners share the same language background. It explores the extent to which code switching plays the roles in enabling students to achieve the pedagogical goals. Also, it attempts to find the place of the functions in the notion of language learning strategy. For second language teaching and learning, the discussion is expected raise teachers’ awareness of the patterns and functions the code switching may have in the teaching and learning process. Therefore, the paper is specifically addressed to teachers of second or foreign language as it will expectedly widen the teachers’ horizon on the fact of code switching existing in language classrooms and help the teachers cope with the phenomenon.